Spatial Distribution and Pattern Analysis of Women Sexual Violence in Tanzania - Mbukwa, Justine N.; Mbegalo, Tukae; Levira, Francis (Springer, Cham, 2024)
Article published by Springer, Cham in the book Health and Medical Geography in Africa pp 247–255